Clinical Significance of Lumbar Puncture in Children with First Febrile Seizures: Cerebrospinal fluid analysis in first febrile seizures - Kim, Yoon Zi; Jung, Hae Woon; Lee, Eun Hye (Iranian Journal of Child Neurology, 2024)
Objectives To evaluate the need for lumbar puncture (LP) in children aged 6 to 60 months experiencing their first febrile seizure, regardless of seizure type, and to determine if LP is particularly beneficial for those under 12 months old. Materials & Methods In this retrospective study, data from 253 children who presented with first febrile seizure were analyzed. All patients in this study underwent LP and were divided into two groups based on their cerebrospinal fluid (CSF) results: non-pleocytosis and pleocytosis. Patients were evaluated for age, sex, familial history of seizure, and type and duration of seizures. They were also evaluated based on laboratory results, including blood tests, CSF analysis, and electroencephalography. Results Sixty-seven (25.9%) of the 253 patients were under 12 months of age, and only two of the 67 patients (2.8%) had pleocytosis. Patients younger than 12 months did not have a higher rate of complex febrile seizure or pleocytosis than those over 13 months of age. None of the patients had bacterial meningitis. Regarding viral meningitis, seven patients (5.3%; age mean SD, 12.3±1.8 months) were diagnosed with enteroviral meningitis, though only one of them had pleocytosis. When compared to the non-pleocytosis group, the pleocytosis group showed no differences in clinical characteristics (age, sex, familial history of seizure, type, and duration of seizure), laboratory results, or the use of antiepileptic drugs. Conclusion The present study suggests that LP should be carefully considered in children with first febrile seizure, including children under 12 months of age